Pelaksanaan Manajemen Konflik di MtsN 1 Tanah Datar - Armizawati armizawati; Suswati Hendriani (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
The main problem in this research is the lack of effectiveness in implementing conflict management by educators, student representatives, BK teachers, and homeroom teachers. This study aims to describe how conflict management plans in solving problems, how to implement conflict management in solving problems, and how to evaluate conflict management in solving student problems at MTsN 1 Tanah Datar. This study used a qualitative analysis which took place at MTsN 1 Tanah Datar. Data collection techniques used are observation, interviews, and documentation. Then to test the validity of the data used is the persistence of the observer, and triangulation. The results of the study indicate that the implementation of conflict management carried out in solving student problems includes planning which at this stage does not directly involve the principal and only general planning, there is no more specific planning, only short-term and long-term programs as conflict management at MTsN 1 Tanah Datar. In the implementation of conflict management which has been going quite well, but there are some things that still need to be considered, such as there are still educators who use violence and do not carry out the steps that have been regulated in conflict management theory in solving student problems.